Penerapan Tema Arsitektur Holistik Pada Perancangan Bangunan Healing Space Di Kota Medan - Nst, Rahmah Yusfah; Budiani, Ina Triesna (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2024)
Dense urban life requires people to fulfill the needs of daily life, resulting in various problems, high daily needs, resulting in various problems. Some of the problems faced such as the demands of the community to work every day, the high cost of living and education, and the competing lifestyles of the community, competing lifestyles between communities, these routines cause community vitality to decline. To overcome this situation, the people of Medan City need recreational facilities in the form of healing space design that aims to provide an alternative recreation for people who want to release their people who want to release fatigue from the busy city, calm their minds, feel a different atmosphere and improve their vitality different atmosphere and improve the mood (vitalis). This healing space building design uses the Holistic Architecture theme approach, where the Holistic Architecture approach pays attention to physical and spiritual factors through the environment approach pays attention to physical and spiritual factors through the built environment.